Pengambilan Keputusan Dalam Organisasi - Ansori Ansori; Alifa Audy Angelya; Naziha Amani; Siti Ainunnisa; Sudirman Sudirman (OPTIMAL Jurnal Ekonomi dan Manajemen, 2024)
In everyday life, we are always presented with many choices that require decisions. Decisions are the result of evaluating various available alternatives. For both individuals and organizations, decision making has a very important role. The decisions taken can have varying levels. Several decision making theories, such as the rational model, normative model, trash can model and bias model, are used to overcome the problems faced. Factors such as individual dynamics, group dynamics and environmental dynamics can also influence the decision-making process carried out by leaders or managers.